Persistent great artery dilatation in Beals syndrome: A novel finding - Saira Siddiqui; Laurie Panesar (Wolters Kluwer Medknow Publications, 2019)
We report a unique case of dilated aortic root and pulmonary artery in an infant with clinical features consistent with Beals syndrome confirmed to have fibrillin-2 mutation. This case highlights a novel finding of main pulmonary artery dilatation that has not been previously reported with Beals syndrome or fibrillin-2 mutation. In addition, the importance of serial echocardiography and consideration of medical management is discussed.